On the identification of Sb2Se3 using Raman scattering. (11th May 2018) - Shongalova, A.; Correia, M.R.; Vermang, B.; Cunha, J.M.V.; Salomé, P.M.P.; Fernandes, P.A.
Abstract: Abstract : Robust evidences are presented showing that the Raman mode around 250 cm −1 in the Sb2 Se3 thin films does not belong to this binary compound. The laser power density dependence of the Raman spectrum revealed the formation of Sb2 O3 for high values of laser intensity power density excitation under normal atmospheric conditions. To complement this study, the Sb2 Se3 films were characterized by x-ray diffraction during in situ annealing. Both these measurements showed that the Sb2 Se3 compound can be replaced by Sb2 O3 . A heat-assisted chemical process explains these findings. Furthermore, Raman conditions required to perform precise measurements are described.